Hubungan Pengetahuan Suami Tentang KB Pria Dengan Keikutsertaan Suami Dalam KB Di Desa Giring Kecamatan Manding Kabupaten Sumenep - Irma Sulistyaningsih (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2019)
this study uses analtycal design by using cross sectional approach. the population of this study is all husbans who are come from fertile couples in Giring manding Sumenep; at about 900 respondents. while the sample which is taken by using simple random sampling technique and than the data are analyzed by using chi-square staistical test. the result of the study showed that almot all of respondents who were not familyplanning acseptors and having less knowladge were 30 respondents (78,9%).